Charitable giving as a signal of trustworthiness: Disentangling the signaling benefits of altruistic acts - Sebastian Fehrler; Wojtek Przepiorka (Institute for the Study of Labor (IZA), 2013)
It has been shown that psychological predispositions to benefit others can motivate human cooperation and the evolution of such social preferences can be explained with kin or multi-level selection models. It has also been shown that cooperation can evolve as a costly signal of an unobservable quality that makes a person more attractive with regard to other types of social interactions. Here we show that if a proportion of individuals with social preferences is maintained in the population through kin or multi-level selection, cooperative acts that are truly altruistic can be a costly signal of social preferences and make altruistic individuals more trustworthy interaction partners in social exchange. In a computerized laboratory experiment, we test whether altruistic behavior in the form of charitable giving is indeed correlated with trustworthiness and whether a charitable donation increases the observing agents' trust in the donor. Our results support these hypotheses and show that, apart from trust, responses to altruistic acts can have a rewarding or outcome-equalizing purpose. Our findings corroborate that the signaling benefits of altruistic acts that accrue in social exchange can ease the conditions for the evolution of social preferences.
Keywords: C72; C92; H41; 330; altruism; evolution of cooperation; costly signaling; social preferences; trust; trustworthiness